Pengaruh Kepuasan Kerja dan Pembinaan Disiplin Terhadap Kinerja Pegawai ASN Pada Dinas X Kabupaten Bandung Barat - Anisa Galih Tanzani; Mochamad Vrans Romi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
High employee performance has a positive impact on both the company and the organization. To improve employee performance, it is important to pay attention to job satisfaction experienced by employees and to consistently implement disciplinary guidance. Based on data on employee absenteeism, it was found that the absenteeism rate of civil servants (ASN) at Department X is relatively high, which is one of the factors affecting employee performance. This study aims to determine the effect of job satisfaction and disciplinary guidance on the performance of civil servants (ASN) at Department X in West Bandung Regency, both partially and simultaneously. The research method used is quantitative, with data collected through questionnaires. The data were analyzed using multiple regression analysis with the help of SPSS version 27.0. The study involved 48 respondents, consisting of 47 civil servants and 1 supervisor. The results show that job satisfaction has a positive effect on employee performance, and disciplinary guidance also has a positive effect on employee performance. Simultaneously, job satisfaction and disciplinary guidance significantly affect employee performance. It can be concluded that the higher the job satisfaction and disciplinary guidance, the better the performance of civil servants at Department X in West Bandung Regency.